The trans‐entorhinal cortex differential depends on retromer‐mediated endosomal recycling. (20th December 2022) - Simoes, Sabrina
Abstract: Anatomical studies have pinpointed the trans‐entorhinal cortex (TEC) as the subregion of the brain selectively vulnerable to Alzheimer's disease. Additional molecular studies have identified endosomal trafficking defects as a cytopathological driver of the disease. However, whether and how endosomal trafficking is linked to anatomical vulnerability still remains unknown. Here, in addressing these questions, we begin by showing that neurons are enriched with a functional distinct retromer core organized around VPS26b, differentially dedicated to endosomal recycling. Using fMRI imaging, and in contrast to its paralog VPS26a, we further demonstrated that depleting VPS26b in mice caused preferential age‐dependent dysfunction in the trans‐entorhinal cortex, a finding further validated by electrophysiology, immunocytochemistry, and behavior. Surprisingly, repletion of VPS26b, both in vitro and in vivo, rescued all phenotypes seen upon VPS26b depletion. We then turned to humans to find VPS26b highly enriched in the TEC region, where both VPS26b and the retromer‐related receptor SORL1 were found deficient in Alzheimer's brains. Finally, by regulating glutamate receptor and SORL1 recycling and its levels, VPS26b was shown to mediate regionally‐selective synaptic dysfunction, as well as AD‐associated amyloid‐precursor protein misprocessing and tau secretion. Together with the trans‐entorhinal's unique network properties, hypothesized to impose a heavy demand on endosomal recycling, these results suggest a general mechanism that can explain AD's regional vulnerability.